Investigation of the psychometric properties of the inclusion body myositis functional rating scale with rasch analysis. Issue 2 (7th June 2019) - Ramdharry, Gita; Morrow, Jasper; Hudgens, Stacie; Skorupinska, Iwona; Gwathmey, Kelly; Currence, Melissa; Herbelin, Laura; Jawdat, Omar; Pasnoor, Mamatha; Mcvey, April; Barohn, Richard J.; Burns, Ted M.; et al.
ABSTRACT: Introduction: The Inclusion Body Myositis Functional Rating Scale (IBMRFS) is a 10‐item clinician‐rated ordinal scale developed for people with inclusion body myositis. Methods: Single observations of the IBMFRS were collected from 132 patients. After Rasch analysis, modifications were made to the scale to optimize fit to the Rasch model while maintaining clinical validity and utility. Results: The original IBMFRS did not fit the assumptions of the Rasch model because of multidimensionality of the scale. Items assessed local dependence, disordered step thresholds, and differential item functioning. Deconstructing the scale into upper limb (IBMFRS‐UL) and lower limb (IBMFRS‐LL) scales improved fit to the Rasch model. A 9‐item scale with the swallowing item removed (IBMFRS‐9) remained multidimensional but demonstrated the ability to discriminate patients along the severity continuum. IBMFRS‐UL, IBMFRS‐LL, and IBMFRS‐9 scores were transformed to a 0–100 scale for comparability. Discussion: This analysis has led to the development of 3 optimized versions of the IBMFRS. Muscle Nerve 60 : 161–168, 2019